Improving the catalytic performance of xylanase from Bacillus circulans through structure-based rational design. (November 2021) - Min, Kyoungseon; Kim, Hoyong; Park, Hyun June; Lee, Siseon; Jung, Ye Jean; Yoon, Ji Hyun; Lee, Jin-Suk; Park, Kyoungmoon; Yoo, Young Je; Joo, Jeong Chan
Graphical abstract: Highlights: Rational engineering of R49 in Bcx xylanase for improving catalytic performance. Saturation mutation of R49 leads to engineering of the active Bcx mutants. R49N exhibits improved catalytic efficiency, thermostability, and thermal activity. R49N produces more xylooligomers from sweet sorghum bagasse than the wild-type. This engineering strategy can be applicable for constructing active enzymes. Abstract: Endo-1, 4-β-xylanase is one of the most important enzymes employed in biorefineries for obtaining fermentable sugars from hemicellulosic components. Herein, we aimed to improve the catalytic performance of Bacillus circulans xylanase (Bcx) using a structure-guided rational design. A systematic analysis of flexible motions revealed that the R49 component of Bcx (i) constrains the global conformational changes essential for substrate binding and (ii) is involved in modulating flexible motion. Site-saturated mutagenesis of the R49 residue led to the engineering of the active mutants with the trade-off between flexibility and rigidity. The most active mutant R49N improved the catalytic performance, including its catalytic efficiency (7.51-fold), conformational stability (0.7 °C improvement), and production of xylose oligomers (2.18-fold higher xylobiose and 1.72-fold higher xylotriose). The results discussed herein can be applied to enhance the catalytic performance of industrially important enzymes by controlling flexibility.